2019
DOI: 10.1111/jch.13560
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive examination of the multilevel adverse risk and protective factors for cardiovascular disease among hypertensive African Americans

Abstract: This paper describes the multilevel factors that contribute to hypertension disparities in 2052 hypertensive African Americans (mean age 52.9 ± 9.9 years; 66.3% female) who participated in a clinical trial. At the family level, participants reported average levels of life chaos and high social support. However, at the individual level, participants exhibited several adverse clinical and behavioral factors including poor blood pressure control (45% of population), obesity (61%), medication non‐adherence (48%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
(112 reference statements)
0
4
0
Order By: Relevance
“…The prevalence of hypertensive TOD in African Americans has been shown to be significantly higher than in non-Hispanic whites (41% vs 28%), more common at an earlier age and more difficult to control in blacks than in whites [ 9 , 10 ]. Several factors may be responsible for the excess TOD associated with hypertension amongst people of African ancestry, including but not limited to differences in salt sensitivity (associated with increased water retention and sodium excretion) [ 11 , 12 ], genetic factors like apolipoprotein A1 (APOL1) polymorphisms [ 13 , 14 ], and circulating cytokines, e.g., transforming growth factor beta (TGF- β ) [ 15 ] and socioeconomic factors [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of hypertensive TOD in African Americans has been shown to be significantly higher than in non-Hispanic whites (41% vs 28%), more common at an earlier age and more difficult to control in blacks than in whites [ 9 , 10 ]. Several factors may be responsible for the excess TOD associated with hypertension amongst people of African ancestry, including but not limited to differences in salt sensitivity (associated with increased water retention and sodium excretion) [ 11 , 12 ], genetic factors like apolipoprotein A1 (APOL1) polymorphisms [ 13 , 14 ], and circulating cytokines, e.g., transforming growth factor beta (TGF- β ) [ 15 ] and socioeconomic factors [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nurses who are well positioned to assist Black women with hypertension in reaching their self-management goals (Jones et al, 2017; Wu & Sheng, 2019) will need specific parameters to guide patients in building a health social network or using an existing peer network. Previous studies have highlighted that Black individuals wanted more support with managing stress from interpersonal relationships (Moss et al, 2019; Wright et al, 2018); therefore, additional studies are needed to determine if health social networks and the number of peers increase risk or are protective (Schoenthaler et al, 2019; Veinot et al, 2011). Future directions of health social networks might include examining the optimal network size, the quality of an individual’s network, and the long- and short-term effects of the networks on health outcomes and health behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Engaging in self-management behaviors, such as changing dietary patterns, participating in exercise behaviors, and adhering to prescribed medication regimens, may help individuals lower their blood pressure and maintain blood pressure control (Blood Pressure Lowering Treatment Trialists' Collaboration, 2021; Tsao et al, 2022). It has been well documented in prior studies that Black women may experience unique barriers to medication adherence and overcoming misconceptions about engaging in hypertension self-management (Braverman & Dedier, 2009; Fongwa et al, 2008; Jones, Moss, et al, 2018; Moss et al, 2019), as well as unique risk factors for cardiovascular disease (Mehta et al, 2023; Schoenthaler et al, 2019). Given the disproportionate hypertension-related morbidity among Black women (e.g., advanced cardiovascular disease, diagnosis of comorbidities, and premature death; Mehta et al, 2023; Tsao et al, 2022), there is a need for targeted approaches to promote self-management strategies to lower blood pressure and improve health outcomes.…”
mentioning
confidence: 99%
“…It is influenced by a number of factors, some of which can be modified [2]. Non-adherence rates have been shown to be associated with age, sex, and race, with lower adherence reported among younger patients [3,4], males [3], low educational level [3], poor health literacy [3], complexity of daily hypertensive regimen [5], persons of color [6], poor relationship with health care provider [4], emotional response to illness [7], lack of appropriate reminders by the family caregiver [8], depression [9] and culture [10,11]. A large study of 1367 outpatients found that knowledge of hypertension, patient satisfaction, and coping skills were significantly associated with medication adherence [2].…”
Section: Introductionmentioning
confidence: 99%